DNA repair proteins may differentiate papillary thyroid cancer from chronic lymphocytic thyroiditis and nodular colloidal goiter - Evren, Bahri; Yilmaz, Sami; Karadag, Nese; Sertkaya, Ayse Cikim; Topaloglu, Omercan; Kilinc, Faruk (Nature Portfolio, 2021)
Malignant thyroid lesions are the most common malignancy of the endocrine glands with increasing rates in the last two decades. Papillary thyroid cancer is the most common thyroid malignancy. In our study, we aimed to quantitatively evaluate the levels of DNA repair proteins MSH2, MLH1, MGMT, which are representative blocks of patients diagnosed with papillary carcinoma, chronic thyroiditis, or colloidal goiter. Total or subtotal thyroidectomy material of 90 patients diagnosed with papillary carcinoma, nodular colloidal goiter, or chronic thyroiditis between 2009 and 2012 were retrospectively evaluated. Tissue samples obtained from paraffin blocks were stained with MGMT, MSH2, MLH1 proteins and their immunohistochemistry was evaluated. Prepared sections were examined qualitatively by an impartial pathologist and a clinician, taking into account the staining method under the trinocular light microscope. Although there was no statistically significant difference in MGMT, MSH2, MLH1, follicular cell positivity, staining intensity, and immunoreactivity values, papillary carcinoma cases showed a higher rate of follicular cell positivity, and this difference was more pronounced between papillary carcinoma and colloidal goiter. In the MSH2 follicular cell positivity evaluation, the difference between chronic thyroiditis and colloidal goiter was significant (p=0.023). The difference between chronic thyroiditis and colloidal goiter was significant in the MSH2 staining intensity evaluation (p=0.001). The difference between chronic thyroiditis and colloidal goiter was significant in MLH1 immunoreactivity evaluation (p=0.012). Papillary carcinoma cases were demonstrated by nuclear staining only for MSH2 and MLH1 proteins as opposed to hyperplastic nodules. The higher levels of expression of DNA repair genes in malignant tumors compared to benign tumors are attributed to the functional activation of DNA repair genes. Further studies are needed for DNA repair proteins to be a potential test in the development and progression of thyroid cancer.
Keywords: Hashimotos-Thyroiditis; Braf Mutation; Carcinoma; Expression; Gene; Mgmt; Metastasis; Children; Lesions